129k views
2 votes
Rewrite the quadratic function in vertex form.
Y=2x^2+4x-1

1 Answer

0 votes

Answer:


\large\boxed{y=2(x+1)^2-3}

Explanation:

The vertex form of an equation of a parabola:


y=a(x-h)^2+k

(h, k) - vertex

We have


y=2x^2+4x-1=2\left(x^2+2x-(1)/(2)\right)

We must use the formula:
(a+b)^2=a^2+2ab+b^2\qquad(*)


2\left(x^2+2(x)(1)-(1)/(2)\right)=2\bigg(\underbrace{x^2+2(x)(1)+1^2}_((*))-1^2-(1)/(2)\bigg)\\\\=2\left((x+1)^2-1-(1)/(2)\right)=2\left((x+1)^2-(3)/(2)\right)

Use the distributive formula a(b + c) = ab + ac


2(x+1)^2+2\left(-(3)/(2)\right)=2(x+1)^2-3

User Tony McCreath
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.